The WAP-buster. - Burns, Simon (Far Eastern Economic Review, 2000)
Part of a special section on the new landscape of the digital future, focusing on Asians leading the digital revolution. A profile of Keiichi Enoki of NTT DoCoMo, who led the team that pushed notoriously sluggish NTT into launching its i-mode Internet-enabled mobile-phone service, is presented. In a mere 18 months, i-mode has attracted more than 10 million subscribers in Japan. Although there is nothing special about the technology involved, i-mode is important because it reminds the world that accessing the Internet through a mobile phone really can work. There has been strong evidence to the contrary from the overhyped and underperforming Wireless Application Protocol (WAP). Another reason why i-mode matters is that its single-bill micropayment system demonstrates a way forward for the Internet, which lacks a good billing system for its most marketable commodity—information. Predictions that i-mode will roll back WAP worldwide and become the de facto standard for mobile Internet access are noted.